1999
DOI: 10.1097/00007632-199908150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Deformity, Pulmonary Compromise, and Quality of Life in Osteogenesis Imperfecta

Abstract: Thoracic scoliosis of more than 60 degrees has severe adverse effects on pulmonary function in those with osteogenesis imperfecta. This finding may partly explain the increased pulmonary morbidity noted in adult patients with osteogenesis imperfecta and scoliosis compared with that in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
2
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 49 publications
5
133
2
8
Order By: Relevance
“…If restrictive or obstructive disease is identified, patients should be managed according to organ specific guidelines. Recent evidence suggests that pulmonary function diminishes in osteogenesis imperfecta with age and lung disease is observed in individuals without scolio sis, suggesting that the lung defect might be intrinsic to the disease and not just the consequence of scoliosis 178,180 .…”
Section: Extraskeletal Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…If restrictive or obstructive disease is identified, patients should be managed according to organ specific guidelines. Recent evidence suggests that pulmonary function diminishes in osteogenesis imperfecta with age and lung disease is observed in individuals without scolio sis, suggesting that the lung defect might be intrinsic to the disease and not just the consequence of scoliosis 178,180 .…”
Section: Extraskeletal Manifestationsmentioning
confidence: 99%
“…The development of progressive scoliosis might lead to pulmonary complications and, in rare cases, the need for ventilation. Baseline and follow up with pulmonary function tests should be performed on all adults with osteogenesis imperfecta 178,180 .…”
Section: Adult Managementmentioning
confidence: 99%
“…Risk of scoliosis in children with the mildest form of OI is 10-fold greater than in the general population [9] and more common even in OI types III and IV [53]. Progression of scoliosis can lead to pulmonary insufficiency [53,54]. For best results, corrective surgery through spinal fusion should be sought when curvature is below 60° [53].…”
Section: Treatmentmentioning
confidence: 99%
“…Widmann et al found that thoracic scoliosis of more than 60°has severe adverse effects on pulmonary function in adults with osteogenesis imperfecta [22]. Therefore, data regarding fatigue and dyspnea should be carefully assessed in childhood as well, and when indicated measurements of pulmonary function should be made.…”
Section: Discussionmentioning
confidence: 99%